Sinonasal Undifferentiated Carcinoma: A 15-Year Single Institution Experience - Workman, Alan D.; Brody, Robert M.; Kuan, Edward C.; Baranov, Esther; Brooks, Steven G.; Alonso-Basanta, Michelle; Newman, Jason G.; Rassekh, Christopher H.; Chalian, Ara A.; Chiu, Alexander G.; Weinstein, Gregory S.; Feldman, Michael D.; Adappa, Nithin D.; O'Malley, Bert W., Jr.; Palmer, James N. (Journal of Neurological Surgery Part B: Skull Base, 2019)
Objective Sinonasal undifferentiated carcinoma (SNUC) is an aggressive neoplasm, with conflicting existing literature regarding prognosis and treatment due to the rarity of disease. Characterization of optimal SNUC management is necessary for improved outcomes.Study Design Case series with planned data collection and analysis.Setting Hospital of the University of Pennsylvania and Pennsylvania Hospital.Participants Patients with pathologically confirmed SNUC treated within a 15-year period were identified, and records were obtained and evaluated for several demographic characteristics.Main Outcomes Measures Disease-specific survival from diagnosis was the primary endpoint, while disease recurrence was a secondary endpoint of the study.Results Twenty-seven patients with established SNUC were included in this cohort, with a median age of 55 years. Eighty-five percent of patients were surgically treated, and 85% of patients presented with stage IV disease. Two-year disease-specific survival was 66% and 5-year disease-specific survival was 46%. Ninety-six percent of patients received both chemotherapy and radiation as adjuvant treatment. Nodal disease at presentation and disease recurrence both significantly decreased patient survival (p < 0.05).Conclusions The majority of patients at this institution presented with clinically advanced disease, and most were managed with a multimodal approach of surgical resection, chemotherapy, and radiation. Extent of disease at presentation and progression of disease following treatment are poor prognostic signs and may merit a more aggressive approach, while early detection and treatment may improve survival and decrease patient morbidity.
Keywords: SNUC; sinonasal undifferentiated carcinoma; survival; treatment paradigms; prognosis